Critical Reviews of R K Narayan’S Literature: A Comprehensive Analysis of R.K. Narayan's Literary Contributions (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The critical reception of R.K.Narayan’s fourteen novels over a period of more than half a century hasestablished him as the most popular of the three founding fathers of the modernIndian novel in English. Nearly 900 publications – monographs and essaycollections, contributions to learned journals and magazines, reviews of singleworks in diverse media, and filmed versions of at least two works – exceed byfar the attention paid  to Mulk RajAnand, or Raja Rao’s achievement. They testify, besides, to the sustainedinterest in Narayan’s narrative oeuvre that ranges from Swami and Friends (1935)to The World of Nagaraj (1989). An overview will give an idea of thenumber of critical responses during the periods 1935-1970, the 1970s, the1980s, and 1990-2004. Besides, it will permit a close look at The Guide (1958),Narayan’s most popular novel. Its literary  innovative  features will  show  that this  story,  though embedded  in  the intermediate period between the latecolonial and the early independence years in India, is a forerunner of thepost-1980s Indian novel in English.